Wśród "Opowiadań kołymskich" Warłama Szałamowa, "Polonistyka" 1994 nr 6, s. 363-369. - Pasterski, Janusz (Wydawnictwa Szkolne i Pedagogiczne, 1994)
Varlam Shalamov`s short stories collectively known as "Kolyma Tales" have been acknowledged by the critics as one of the most interesting texts depicting the experience thousands od prisoners od Soviet labor camps. The paper discusses the multidimensional structure of the short stories and stresses the role of the main characters.
Artykuł w czasopiśmie "Polonistyka" 1994 nr 6, s. 363-369.
Keywords: Warłam Szałamow; literatura łągrowa; literatura rosyjska; opowiadania; nowelistyka; Gułag